Discussing Patient Emotions in Audiology: Provider Experiences With the Implementation Process of Hearing Loss Psychological Inflexibility Screenings - Grigsby, Sydnee; Muñoz, Karen; San Miguel, Guadalupe G; Twohig, Michael P (American journal of audiology, 2024)
This study aimed to investigate barriers and facilitators experienced by clinical educators and graduate students when talking with patients about difficult emotions and thoughts related to their hearing. A longitudinal observational design was used and an Implementation Research Logic Model guided the process. Five clinical educators and five graduate students participated in the study. Participants completed pre- and postmeasures and attended individual debriefing sessions during the 8-month study period. Four themes emerged from the debriefing sessions: (a) learning process, (b) confidence, (c) barriers, and (d) supervision. Participants described that the Acceptance and Action Questionnaire-Managing Child Hearing Loss and Acceptance and Action Questionnaire-Adult Hearing Loss served as a reminder to ask about patients' internal barriers and increased awareness of their discomfort in talking about patient emotions. Participants also described barriers and struggles related to supporting students in gaining counseling skills. Screening for internal challenges helped clinicians remember to talk with patients about their difficult thoughts and emotions. Clinician hesitancy to engage in conversations with patients about their emotions can interfere with opportunities for patients to share their struggles and with training student in these skills.